Exploration of Jlamprang Batik Motifs using Digital Printing Techniques to Apply Please on Men's Shirt - Azaroh, Binti; Suhartini, Ratna (East Asian Journal of Multidisciplinary Research, 2024)
This research aims to find out 1) the development of the jlamprang batik motif, 2) the application and placement of pleats on men's shirts with the jlamprang batik motif, and 3) the finished results of the exploration of the jlamprang batik motif using digital printing techniques to apply pleats to men's shirts. This type of research is quantitative descriptive. Data collection is carried out using questionnaires or questionnaires. The instrument scale used is the Likert scale rating. The data analysis technique used is average value. This research resulted in a description of the process of developing the jlamprang batik motif, the application and placement of pleats on men's shirts with jlamprang batik motifs, the result was an exploration of the jlamprang batik motif using digital printing techniques to apply pleats to men's shirts.